Social Insects—II. Bees and Wasps - KACHROO, P. (SCHOOL SCIENCE, 2006)
Bees lives in permanent communities.Their body has a marked waist. The head and thorax bear branched feathery projections which help them in collecting pollen from flowers. These projections cannot be seen by the naked eye but this character distinguishes bees from wasps. The honey bees have three types of individuals: males (drones), females (queens), and sterile females (workers) (Fig. 1). It is interesting to note that distinction between queens and workers is caused by the different food with which the larvae are fed. After hatching, the brood are fed alike for the first four days. Later, some i.e., the would-be queens are fed with richer food throughout their growth. They are finally provided with cells which are larger and better ventilated.